Perception management in the media - DERMAN, GİRAY SAYNUR (My University, 2021)
Information, transmitted through communication or media, plays an important role in the communication between individuals and communities. This information raises awareness about the events. On the other hand, information in news is not always conveyed correctly. The inaccurate transfer of information as incomplete or destroyed, on purpose, is an example of disinformation. This process constitutes an important part of social perception management in the media, especially in the discourse of war and peace. Though perception management has been used throughout human history, it became a concept within the 20th century. It was the US Department of Defense to conceptualize this method for the first time but later on it it increased its popularity day by day in the 21st century, which is also known as the age of technology. People's easy and quick access to information causes the same amount of information pollution, and this situation makes perceptions affected by many factors making them vulnerable to external interventions. As a result, perceptions can be easily manipulated, mass movements can be created, and social events can be easily manipulated. In this context, perception management, which has become more and more important day by day, attracts the attention of individuals, states, companies and institutions and organizations such as civil society. In the study, textual, linguistic and visual elements in war discourse were examined with the method of content analysis. In this article, definition of perception, its process and factors affecting to it are discussed, and the conceptual and historical background of perception management is conveyed.
Keywords: Perception Management; Social Media; Propaganda; Mass Movement; Manipulation